Factores de incidencia del gobierno electrónico en los procesos de transparencia y participación ciudadana caso de análisis: GAD Municipal de Pujilí - Andino Moscoso, Karen Celeste (2023)
This titling work called Factors of incidence of the electronic government in the processes of transparency and citizen participation case of analysis: GAD Municipal de Pujilí, has as objectives: to analyze the conceptual-theoretical aspects of the electronic government associated with transparency and citizen participation, to identify the factors of electronic government that affect the aspects indicated in this institution, establish mechanisms in the electronic government of the GAD of Pujilí that contribute to the improvement of transparency and citizen participation.